A Direct Titrimetric Determination of Malic, Tartaric and Thiolycollic Acids with Ammonium Hexanitratocerate(IV) - Madhava Rao, B.; Desai, K.P.; Kulkarni, M.J. (Asian Journal of Chemistry, 2010)
The use of ammonium hexanitratocerate (IV) in oxidimetry has not been studied in considerable detail, although the salt can be obtained in a high degree of purity. Conditions have now been established for the direct and also reverse titration of malic, tartaric and thioglycollic acids with this reagent at room temperature and also slightly elevated temperatures in nitric acid medium using ferroin as indicator. The procedures developed give reasonably precise results and they constitute a definite improvement over those involving cerium (IV) sulphate.